High-strength corrosion-resistant ship cable and preparation method thereof
By using modified basalt fibers and new flame retardants in ship cables, combined with polyvinyl chloride and nitrile rubber, the problem of difficult ship cables to meet high standards in harsh environments is solved, achieving high strength, corrosion resistance and resistance The combustion performance extends the service life of the cable.
Patent Information
- Application Number
- CN202411673341.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing ship cables are difficult to meet high standards such as anti-interference, corrosion, salt spray, waterproof, oil resistance, wear resistance, oxidation resistance and mechanical strength in harsh ship environments, and traditional materials have poor weather resistance and aging resistance. It can easily lead to short circuits and fire risks.
Using modified basalt fibers and new flame retardants, the macromolecular antioxidants and hexachlorocyclic triphosphazene and DOPO are grafted on the surface of basalt fibers through chemical reactions to synthesize flame retardants with DOPO, combining polyvinyl chloride and nitrile rubber to form high Sheath layer with strength, salt spray corrosion resistance and flame retardant.
It improves the mechanical properties, thermal oxygen aging resistance and flame retardant properties of the cable, extends the service life, enhances the tolerance to complex environments, and avoids the volatility and migration of antioxidants.
Smart Images

Figure CN119320538A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables, and in particular relates to a high-strength corrosion-resistant ship cable and a preparation method thereof. Background Art
[0002] Marine cables are special wires and cables for power, lighting, control, communication, microcomputer and other systems of various ships, offshore oil platforms and water buildings. Due to the harsh operating environment, the cables are required to be safe and reliable, long life, small size, light weight, and have excellent heat resistance, fire resistance, flame retardancy, oil resistance, moisture resistance, seawater resistance, excellent electrical and mechanical properties, etc., among which marine cables are a type of marine cables.
[0003] The communication cables used in the ship environment need to meet the requirements of strong anti-interference ability, corrosion resistance, salt spray resistance, waterproof, oil resistance, wear resistance, oxidation resistance, high mechanical strength and electrical insulation, long service life and high reliability in complex environments. It is difficult to meet high standards by using ordinary materials to process this cable. The traditional cable sheath layer uses polyolefins. Although it has high electrical strength, it has poor corrosion resistance, flame retardancy and aging resistance. Although the rubber sheath layer is soft, it has poor weather resistance, aging resistance and flame resistance. The cable will be damaged by environmental influences during use, which will cause short circuit of the cable and cause fire and other hazards. In addition, the cable will be damaged under stress conditions such as bending and rolling for a long time, and the pressure resistance is poor, which is not convenient for use. Summary of the invention
[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a high-strength corrosion-resistant ship cable and a preparation method thereof. By adding modified basalt fiber and a new flame retardant, the cable is endowed with excellent mechanical properties, salt spray corrosion resistance, thermal oxidation aging resistance and flame retardant properties.
[0005] The purpose of the present invention can be achieved by the following technical solutions: A high-strength corrosion-resistant ship cable comprises a conductor core, an insulating layer wrapped outside the conductor core, a shielding layer wrapped outside the insulating layer, and a sheath layer wrapped outside the shielding layer, wherein the sheath layer comprises the following components in parts by weight: 40 to 55 parts of polyvinyl chloride, 20 to 30 parts of nitrile rubber, 5 to 15 parts of modified basalt fiber, 3 to 8 parts of flame retardant, 1 to 2 parts of lubricant, and 0.1 to 1 part of light stabilizer; The modified basalt fiber is prepared by grafting a macromolecular antioxidant on the surface of the basalt fiber by chemical reaction. The structural formula of the macromolecular antioxidant is as follows: ; The flame retardant is prepared by performing a first step nucleophilic substitution reaction on hexachlorocyclotriphosphazene and DOPO, and then using a terminal hydroxyl phosphorus-containing intermediate as a linker to replace the remaining chlorine atoms in the hexachlorocyclotriphosphazene.
[0006] Preferably, the insulating layer uses cross-linked polyethylene or polyethylene as the insulating material; the shielding layer includes a first shielding layer and a second shielding layer, the first shielding layer is made of aluminum foil wrapping, and the second shielding layer is made of silver-plated copper wire weaving.
[0007] Preferably, the lubricant is polyethylene wax or oxidized polyethylene wax; the light stabilizer is one or more combinations of light stabilizer 2020, light stabilizer 770, and light stabilizer 944.
[0008] Preferably, the preparation method of the sheath layer material comprises the following steps: weighing each raw material by weight, putting polyvinyl chloride and nitrile rubber into an internal mixer and plasticizing for 2 to 3 minutes to obtain a premix, then adding modified basalt fiber, flame retardant, lubricant and light stabilizer and mixing evenly to obtain a mixture, putting the mixture into a twin-screw extruder for extrusion molding, and preparing the sheath layer material.
[0009] Preferably, the method for preparing the modified basalt fiber comprises the following steps: A. Put basalt fiber and hydrogen peroxide solution in a reactor, slowly add concentrated sulfuric acid under stirring, place at 30-45°C for reaction for 1-1.5h, then heat to 60-70°C for further reaction for 10-12h, wash with deionized water and filter after the reaction, then place in an oven for drying to obtain pretreated basalt fiber; B. Take anhydrous ethanol, deionized water and γ-aminopropyltriethoxysilane, place them at 45-60°C for hydrolysis to obtain a silane hydrolyzate, then add the silane hydrolyzate to the pretreated basalt fiber and stir to react for 0.5-1h. After the reaction is completed, filter, wash and dry to obtain the amino basalt fiber; C. Take a macromolecular antioxidant and dissolve it in cyclohexanone, then add the amino basalt fiber and disperse it ultrasonically, place it at room temperature and stir to react for 3 to 5 hours. After the reaction is completed, filter, wash and dry to obtain modified basalt fiber.
[0010] Preferably, the method for preparing the macromolecular antioxidant in step C comprises the following steps: C1. Dissolve 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid and 3-butene-1-ol in dichloromethane, stir and mix at 0-4°C in a nitrogen atmosphere, then add 4-dimethylaminopyridine and continue stirring to obtain a mixed solution, dissolve N,N-dicyclohexylcarbodiimide in dichloromethane and add to the mixed solution, react at room temperature for 42-48 hours, and after the reaction is completed, pour the reaction solution into deionized water, filter and evaporate to obtain a crude product, then perform chromatography separation, eluent elution, and reduced pressure evaporation to obtain 3-butene-1-yl-3,5-di-tert-butyl-4-hydroxyphenylpropionic acid ester; C2. Take 3-butene-1-yl-3,5-di-tert-butyl-4-hydroxyphenylpropionate, N-phenylmaleimide and maleic anhydride and dissolve them in cyclohexanone. Protect the reaction with nitrogen. Stir at 45-65°C for 5-15 minutes. Then add azobisisobutyronitrile and heat to 95-110°C for 3-6 hours. After the reaction is completed, pour the reaction solution into petroleum ether and filter and dry to obtain a macromolecular antioxidant.
[0011] Preferably, in step C1, the molar ratio of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid to 3-butene-1-ol is 1:0.8-1; in step C2, the molar ratio of 3-butene-1-yl-3,5-di-tert-butyl-4-hydroxyphenylpropionic acid ester, N-phenylmaleimide and maleic anhydride is 1:1:1-1.2.
[0012] Preferably, the method for preparing the flame retardant comprises the following steps: (1) Phenylphosphoryl dichloride and diethylene glycol are placed in a reactor filled with tetrahydrofuran, triethylamine is added, and the mixture is stirred at room temperature for 5 to 7 hours. After the reaction is completed, the mixture is filtered, rotary evaporated, and dried to obtain a terminal hydroxyl phosphorus intermediate; (2) Put hexachlorocyclotriphosphazene in a reactor, add acetone and ultrasonically dissolve it to obtain solution 1, dissolve DOPO in acetone to obtain solution 2, dissolve the terminal hydroxyl phosphorus intermediate in acetone to obtain solution 3, place the reactor in a 25-30°C oil bath, add solution 2 and triethylamine, stir and react for 10-12 hours, then raise the temperature to 45-60°C, add solution 3 and triethylamine, stir and react for 10-12 hours, and after the reaction is completed, filter, wash and dry to obtain a flame retardant.
[0013] Preferably, in step (1), the molar ratio of phenylphosphoryl dichloride to diethylene glycol is 1:2.5-2.7; and in step (2), the molar ratio of hexachlorocyclotriphosphazene, DOPO and the terminal hydroxyl phosphorus-containing intermediate is 1:3-3.4:3-3.5.
[0014] The method for preparing the high-strength corrosion-resistant ship cable as described above comprises the following steps: S1. Using a wire drawing machine to draw the copper rod to obtain a copper wire, and then annealing the wire to obtain a conductor; S2, twisting at least two of the conductors together to obtain a conductor core; S3, using an extruder to extrude an insulating layer on the outer surface of the conductor core; S4, wrap aluminum foil around the outer surface of the insulation layer to obtain a first shielding layer, and cross-weave silver-plated copper wire on the outer surface of the first shielding layer to obtain a second shielding layer; S5. Extruding a sheath layer on the outer surface of the second shielding layer to prepare a high-strength, corrosion-resistant ship cable.
[0015] Beneficial effects of the present invention: The sheath layer of the invention adopts polyvinyl chloride and nitrile rubber as main materials. The nitrile rubber has excellent oil resistance, heat resistance and physical and mechanical properties. The nitrile rubber is used to reinforce the polyvinyl chloride. The invention pre-treats basalt fiber to obtain basalt fiber with activated surface hydroxyl groups, and then uses silanol groups hydrolyzed from gamma-aminopropyltriethoxysilane to react with hydroxyl groups on the surface of the pre-treated basalt fiber to obtain amino basalt fiber. Meanwhile, the invention uses 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid and 3-butene-1-ol to react to synthesize a small molecule antioxidant 3-butene-1-yl-3,5-di-tert-butyl-4-hydroxyphenylpropionate with a double bond structure on the surface, and then obtains a macromolecular antioxidant by free radical copolymerization of the small molecule antioxidant, N-phenylmaleimide and maleic anhydride. The macromolecular antioxidant contains three rigid groups of imide, maleic anhydride and benzene ring, and has an inhibitory effect on the movement and rotation of molecular chains. The maleic anhydride group in the structure of the macromolecular antioxidant reacts with the amino group on the surface of the amino basalt fiber, so that the macromolecular antioxidant is grafted onto the surface of the basalt fiber to prepare the modified basalt fiber. Among them, basalt fiber is an inorganic, environmentally friendly, green, high-performance fiber material with the characteristics of high elastic modulus, high tensile strength, high wear resistance, excellent high temperature resistance and corrosion resistance. The macromolecular antioxidant is firmly combined with the basalt fiber through chemical bonds. The synthesis of macromolecular antioxidants is beneficial to improving the cable's resistance to thermal oxidation aging, while avoiding the problem of easy volatilization, migration and extraction of antioxidants during processing or long-term use. The prepared modified basalt fiber has good dispersibility and strong interface bonding force.
[0016] The invention uses phenylphosphoryl dichloride and diethylene glycol to react to obtain a terminal hydroxyl phosphorus-containing intermediate, then uses hexachlorocyclotriphosphazene, DOPO and the terminal hydroxyl phosphorus-containing intermediate as raw materials, and makes the PH bond contained in DOPO replace one of the chlorine atoms connected to each phosphorus atom on the hexachlorocyclotriphosphazene under the action of polar solvent acetone and acid binding agent triethylamine, and then uses the terminal hydroxyl phosphorus-containing intermediate as a connector to make the hydroxyl group contained in the intermediate and the remaining chlorine atoms on the hexachlorocyclotriphosphazene undergo substitution reaction, so as to prepare a polymer flame retardant and give the cable more excellent flame retardant performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 It is a schematic structural diagram of the high-strength corrosion-resistant ship cable of the present invention.
[0019] In the figure: 1- conductor core, 2- insulation layer, 3- shielding layer, 4- sheath layer. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] like Figure 1 As shown, a high-strength corrosion-resistant ship cable comprises a conductor core 1, an insulating layer 2 wrapped around the conductor core 1, a shielding layer 3 wrapped around the insulating layer 2, and a sheath layer 4 wrapped around the shielding layer 3; A method for preparing a high-strength corrosion-resistant ship cable comprises the following steps: S1. Using a wire drawing machine to draw the copper rod to obtain a copper wire, and then annealing the wire to obtain a conductor; S2, twisting at least two of the conductors together to obtain a conductor core; S3, using an extruder to extrude an insulating layer on the outer surface of the conductor core; S4, wrap aluminum foil around the outer surface of the insulation layer to obtain a first shielding layer, and cross-weave silver-plated copper wire on the outer surface of the first shielding layer to obtain a second shielding layer; S5. Extruding a sheath layer on the outer surface of the second shielding layer to prepare a high-strength, corrosion-resistant ship cable.
[0022] Example 1 A method for preparing modified basalt fiber comprises the following steps: A. Take 2g of basalt fiber and 30mL of 30% hydrogen peroxide solution in a reactor, slowly add 57mL of concentrated sulfuric acid under stirring, place at 40℃ for reaction for 1h, then heat to 70℃ and continue to react for 12h. After the reaction is completed, wash with deionized water and filter, then place in an oven for drying to obtain pretreated basalt fiber; B. Take 15 mL of anhydrous ethanol, 35 mL of deionized water and 5 mL of γ-aminopropyltriethoxysilane, place them at 50°C for hydrolysis to obtain a silane hydrolyzate, then add 2 g of pretreated basalt fiber to the silane hydrolyzate and stir for 1 hour. After the reaction is completed, filter, wash and dry to obtain amino basalt fiber; C. Take 4.2g of macromolecular antioxidant and dissolve it in 60mL of cyclohexanone, then add 2g of amino basalt fiber and disperse it ultrasonically, place it at room temperature and stir to react for 5h. After the reaction is completed, filter, wash and dry to obtain modified basalt fiber.
[0023] The preparation method of the macromolecular antioxidant comprises the following steps: C1. Dissolve 5.22g of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid and 1.09g of 3-butene-1-ol in 80mL of dichloromethane, stir and mix at 0°C in a nitrogen atmosphere, then add 0.19g of 4-dimethylaminopyridine and continue stirring to obtain a mixed solution, dissolve 4.64g of N,N-dicyclohexylcarbodiimide in 10mL of dichloromethane and add to the mixed solution, react at room temperature for 48h, and after the reaction is completed, pour the reaction solution into deionized water, filter and evaporate to obtain a crude product, and then separate the crude product by silica gel column chromatography, elute with an eluent (ethyl acetate / cyclohexanone=1:9), and evaporate the eluent under reduced pressure to obtain 3-butene-1-yl-3,5-di-tert-butyl-4-hydroxyphenylpropionic acid ester; C2. Take 4.15g of 3-butene-1-yl-3,5-di-tert-butyl-4-hydroxyphenylpropionate, 2.16g of N-phenylmaleimide and 1.23g of maleic anhydride and dissolve them in 50mL of cyclohexanone. Protect the reaction with nitrogen. Stir at 55°C for 10min. Then add 0.08g of azobisisobutyronitrile. Heat to 105°C and react for 4h. After the reaction is completed, pour the reaction solution into petroleum ether and filter and dry to obtain a macromolecular antioxidant.
[0024] Example 2 A method for preparing a flame retardant comprises the following steps: (1) 2 g of phenylphosphoryl dichloride and 2.72 g of diethylene glycol were placed in a reactor containing 100 mL of tetrahydrofuran, and 2.17 g of triethylamine was added in batches to remove the hydrogen chloride produced by the reaction. The mixture was stirred at room temperature for 6 h. After the reaction was completed, the mixture was filtered, rotary evaporated, and dried to obtain a terminal hydroxyl phosphorus intermediate. (2) Take 3.48g of hexachlorocyclotriphosphazene in a reactor, add 50mL of acetone and ultrasonically dissolve it to obtain solution 1, take 6.52g of DOPO and dissolve it in 100mL of acetone to obtain solution 2, take 7.95g of terminal hydroxyl phosphorus intermediate and dissolve it in 100mL of acetone to obtain solution 3, place the reactor in a 30℃ oil bath, add solution 2 and 3mL of triethylamine, stir and react for 12h, then raise the temperature to 55℃, add solution 3 and 5mL of triethylamine, stir and react for 12h, after the reaction is completed, filter, wash and dry to obtain a flame retardant.
[0025] Example 3 A sheath layer includes the following components in parts by weight: 42 parts of polyvinyl chloride, 21 parts of nitrile rubber, 5 parts of modified basalt fiber prepared in Example 1, 3 parts of flame retardant prepared in Example 2, 1 part of lubricant polyethylene wax, and 0.2 parts of light stabilizer 2020.
[0026] The preparation method of the above-mentioned sheath layer material comprises the following steps: weighing each raw material by weight, putting polyvinyl chloride and nitrile rubber into an internal mixer and plasticizing for 3 minutes to obtain a premix, then adding modified basalt fiber, flame retardant, lubricant and light stabilizer and mixing evenly to obtain a mixture, putting the mixture into a twin-screw extruder for extrusion molding, and preparing the sheath layer material.
[0027] Example 4 A sheath layer includes the following components in parts by weight: 47 parts of polyvinyl chloride, 25 parts of nitrile rubber, 10 parts of modified basalt fiber prepared in Example 1, 5 parts of flame retardant prepared in Example 2, 2 parts of lubricant oxidized polyethylene wax, and 0.5 parts of light stabilizer 770.
[0028] The preparation method of the above-mentioned sheath layer material is the same as that of Example 3.
[0029] Example 5 A sheath layer includes the following components in parts by weight: 54 parts of polyvinyl chloride, 30 parts of nitrile rubber, 15 parts of modified basalt fiber prepared in Example 1, 8 parts of flame retardant prepared in Example 2, 2 parts of lubricant oxidized polyethylene wax, and 1 part of light stabilizer 944.
[0030] The preparation method of the above-mentioned sheath layer material is the same as that of Example 3.
[0031] Comparative Example 1 A sheath layer includes the following components in parts by weight: 54 parts of polyvinyl chloride, 30 parts of nitrile rubber, 15 parts of basalt fiber, 8 parts of the flame retardant prepared in Example 2, 2 parts of lubricant oxidized polyethylene wax, and 1 part of light stabilizer 944.
[0032] The preparation method of the above-mentioned sheath layer material is the same as that of Example 3.
[0033] Comparative Example 2 A sheath layer includes the following components in parts by weight: 54 parts of polyvinyl chloride, 30 parts of nitrile rubber, 15 parts of modified basalt fiber prepared in Example 1, 2 parts of lubricant oxidized polyethylene wax, and 1 part of light stabilizer 944.
[0034] The preparation method of the above-mentioned sheath layer material is the same as that of Example 3.
[0035] Performance Testing (1) Mechanical properties and flame retardant properties test: The sheath layer materials prepared in Examples 3-5 and Comparative Examples 1-2 were subjected to a tensile properties test using a universal mechanical testing machine in accordance with GB / T 1040.2-2022, with a sample size of 100 mm×5 mm×3.5 mm. The impact strength test was performed in accordance with GB / T1843-2008, with a sample size of 80 mm×10 mm×4 mm. The flame retardant properties were tested using a limiting oxygen index test (LOI) and a vertical burning test (UL94). The standard used for the limiting oxygen index test was ASTM D2863, with a sample size of 130 mm×6.5 mm×3.2 mm. The standard used for the vertical burning test was ASTMD3801-2010, with a sample size of 130 mm×13 mm×3.2 mm. The data results are shown in Table 1.
[0036] Table 1 Test results of mechanical properties and flame retardant properties of samples
[0037] It can be seen from the data in Table 1 that the sheath layer materials prepared in Examples 3-5 of the present invention are not easy to break and have high impact strength. In Comparative Example 1, the basalt fiber was not modified, and its measured mechanical properties were worse than those of Examples 3-5, which may be due to the poor dispersibility of the basalt fiber and the low interface bonding strength with the matrix, which limited the full play of its mechanical properties. In Comparative Example 2, no flame retardant was added, and its measured mechanical properties were slightly higher than those of Examples 3-5, indicating that the addition of flame retardant has a certain effect on the mechanical properties of the material, but the addition of flame retardant greatly improves the flame retardant properties of the material, UL-94 reaches V-0 and LOI is significantly increased.
[0038] (2) Salt spray resistance test: The sheath layer materials prepared in Examples 3-5 and Comparative Examples 1-2 were subjected to salt spray resistance test. The salt spray test temperature was 35°C, the mass fraction of sodium chloride was 5%, and the test time was 128 hours. The change rates of tensile strength and elongation at break were tested, and the data results are shown in Table 2.
[0039] Table 2 Test results of salt spray resistance of samples
[0040] It can be seen from the data in Table 2 that the sheath layer materials prepared in Examples 3-5 of the present invention and Comparative Example 2 have excellent salt spray resistance. In Comparative Example 1, the basalt fiber was not modified, and the change rates of tensile strength and elongation at break changed significantly.
[0041] (3) Aging performance test: The sheath layer materials prepared in Examples 3-5 and Comparative Examples 1-2 were aged at 100° C. for 24 h and 48 h, respectively, and then their tensile strength and elongation at break were tested. The data results are shown in Table 3.
[0042] Table 3 Test results of thermal oxygen aging performance of samples
[0043] It can be seen from the data in Table 3 that the sheath layer materials prepared in Examples 3-5 of the present invention still have high tensile strength and elongation at break after aging for 24h and 48h, indicating that the sheath layer materials have excellent resistance to heat and oxygen aging. In Comparative Example 1, the basalt fiber was not modified, and the tensile strength and tear strength of the sheath layer material decreased significantly after aging.
[0044] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0045] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A high-strength corrosion-resistant ship cable, characterized in that: It comprises a conductor core, an insulating layer wrapped outside the conductor core, a shielding layer wrapped outside the insulating layer, and a sheath layer wrapped outside the shielding layer, wherein the sheath layer comprises the following components in parts by weight: 40-55 parts of polyvinyl chloride, 20-30 parts of nitrile rubber, 5-15 parts of modified basalt fiber, 3-8 parts of flame retardant, 1-2 parts of lubricant, and 0.1-1 part of light stabilizer; The modified basalt fiber is made by grafting a macromolecular antioxidant on the surface of the basalt fiber by chemical reaction. The structural formula of the macromolecular antioxidant is as follows: ; The flame retardant is prepared by performing a first step nucleophilic substitution reaction on hexachlorocyclotriphosphazene and DOPO, and then using a terminal hydroxyl phosphorus-containing intermediate as a linker to replace the remaining chlorine atoms in the hexachlorocyclotriphosphazene.
2. The high-strength corrosion-resistant ship cable according to claim 1, characterized in that: The insulating layer uses cross-linked polyethylene or polyethylene as the insulating material; the shielding layer includes a first shielding layer and a second shielding layer, the first shielding layer is made of aluminum foil wrapping, and the second shielding layer is made of silver-plated copper wire weaving.
3. The high-strength corrosion-resistant ship cable according to claim 1, characterized in that: The lubricant is polyethylene wax or oxidized polyethylene wax; the light stabilizer is one or more combinations of light stabilizer 2020, light stabilizer 770, and light stabilizer 944.
4. The high-strength corrosion-resistant ship cable according to claim 1, characterized in that: The preparation method of the sheath layer material comprises the following steps: weighing each raw material by weight, putting polyvinyl chloride and nitrile rubber into an internal mixer and plasticizing for 2-3 minutes to obtain a premix, then adding modified basalt fiber, flame retardant, lubricant and light stabilizer and mixing evenly to obtain a mixture, putting the mixture into a twin-screw extruder for extrusion molding, and preparing the sheath layer material.
5. The high-strength corrosion-resistant ship cable according to claim 1, characterized in that: The preparation method of the modified basalt fiber comprises the following steps: A. Put basalt fiber and hydrogen peroxide solution in a reactor, slowly add concentrated sulfuric acid under stirring, place at 30-45°C for reaction for 1-1.5h, then heat to 60-70°C for further reaction for 10-12h, wash with deionized water and filter after the reaction, then place in an oven for drying to obtain pretreated basalt fiber; B. Take anhydrous ethanol, deionized water and γ-aminopropyltriethoxysilane, place them at 45-60°C for hydrolysis to obtain a silane hydrolyzate, then add the silane hydrolyzate to the pretreated basalt fiber and stir to react for 0.5-1h. After the reaction is completed, filter, wash and dry to obtain the amino basalt fiber; C. Take a macromolecular antioxidant and dissolve it in cyclohexanone, then add the amino basalt fiber and disperse it ultrasonically, place it at room temperature and stir to react for 3 to 5 hours. After the reaction is completed, filter, wash and dry to obtain modified basalt fiber.
6. The high-strength corrosion-resistant ship cable according to claim 5, characterized in that: The method for preparing the macromolecular antioxidant in step C comprises the following steps: C1. Dissolve 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid and 3-butene-1-ol in dichloromethane, stir and mix at 0-4°C in a nitrogen atmosphere, then add 4-dimethylaminopyridine and continue stirring to obtain a mixed solution, dissolve N,N-dicyclohexylcarbodiimide in dichloromethane and add to the mixed solution, react at room temperature for 42-48 hours, and after the reaction is completed, pour the reaction solution into deionized water, filter and evaporate to obtain a crude product, then perform chromatography separation, eluent elution, and reduced pressure evaporation to obtain 3-butene-1-yl-3,5-di-tert-butyl-4-hydroxyphenylpropionic acid ester; C2. Take 3-butene-1-yl-3,5-di-tert-butyl-4-hydroxyphenylpropionate, N-phenylmaleimide and maleic anhydride and dissolve them in cyclohexanone. Protect the reaction with nitrogen. Stir at 45-65°C for 5-15 minutes. Then add azobisisobutyronitrile and heat to 95-110°C for 3-6 hours. After the reaction is completed, pour the reaction solution into petroleum ether and filter and dry to obtain a macromolecular antioxidant.
7. The high-strength corrosion-resistant ship cable according to claim 6, characterized in that: In the step C1, the molar ratio of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid to 3-butene-1-ol is 1:0.8-1; in the step C2, the molar ratio of 3-butene-1-yl-3,5-di-tert-butyl-4-hydroxyphenylpropionic acid ester, N-phenylmaleimide and maleic anhydride is 1:1:1-1.
2.
8. The high-strength corrosion-resistant ship cable according to claim 1, characterized in that: The preparation method of the flame retardant comprises the following steps: (1) Phenylphosphoryl dichloride and diethylene glycol are placed in a reactor filled with tetrahydrofuran, triethylamine is added, and the mixture is stirred at room temperature for 5 to 7 hours. After the reaction is completed, the mixture is filtered, rotary evaporated, and dried to obtain a terminal hydroxyl phosphorus intermediate; (2) Put hexachlorocyclotriphosphazene in a reactor, add acetone and ultrasonically dissolve it to obtain solution 1, dissolve DOPO in acetone to obtain solution 2, dissolve the terminal hydroxyl phosphorus intermediate in acetone to obtain solution 3, place the reactor in a 25-30°C oil bath, add solution 2 and triethylamine, stir and react for 10-12 hours, then raise the temperature to 45-60°C, add solution 3 and triethylamine, stir and react for 10-12 hours, and after the reaction is completed, filter, wash and dry to obtain a flame retardant.
9. The high-strength corrosion-resistant ship cable according to claim 8, characterized in that: In the step (1), the molar ratio of phenylphosphoryl dichloride to diethylene glycol is 1:2.5-2.7; in the step (2), the molar ratio of hexachlorocyclotriphosphazene, DOPO and the terminal hydroxyl phosphorus-containing intermediate is 1:3-3.4:3-3.
5.
10. The method for preparing a high-strength corrosion-resistant ship cable according to claim 1, characterized in that: The following steps are involved: S1. Using a wire drawing machine to draw the copper rod to obtain a copper wire, and then annealing the wire to obtain a conductor; S2, twisting at least two of the conductors together to obtain a conductor core; S3, using an extruder to extrude an insulating layer on the outer surface of the conductor core; S4, wrap aluminum foil around the outer surface of the insulation layer to obtain a first shielding layer, and cross-weave silver-plated copper wire on the outer surface of the first shielding layer to obtain a second shielding layer; S5. Extruding a sheath layer on the outer surface of the second shielding layer to prepare a high-strength, corrosion-resistant ship cable.
Citation Information
Patent Citations
Marine flame-retardant corrosion-resistant polyurethane cable sheath material
CN108841162A
Low-smoke ceramic cable and preparation process thereof
CN110294905A
Long-acting anti-oxidation and corrosion-resistant cable material and preparation method thereof
CN110423383A
Offshore photovoltaic cable insulating sheath material and preparation method thereof
CN118006025A
Anti-tear flame-retardant cable and preparation method thereof
CN118206832A
Cited By
Fire-resistant cable and preparation method thereof
CN121148807A
Flame-resistant modified polymer copper conductor cable and manufacturing process thereof
CN121355034A
Wear-resistant tensile power cable and preparation method thereof
CN121862510A